Anatomical and physiological responses of arsenic hyperaccumulating water Spinach (Ipomoea Aquatica) (Bangladesh Journal of Botany, 2026)
Phytoremediation is reported to be a highly efficient and environmentally friendly method for cleaning up soils contaminated with metals and metalloids. The potential of water spinach (Ipomoea aquatica) as a hyperaccumulator plant has been investigated through physiological and anatomical adaptations during this study. Three concentrations of arsenic (As), namely 50, 100, and 150 µM, along with a mock treatment, were tested at 15 and 30 days of treatment. Due to As application, the plants exhibited stunted growth, characterized by reduced plant height and weight compared to the controls. Additionally, As toxicity led to a decrease in chlorophyll content in the leaves of water spinach. Although the total protein content increased in roots treated with 50 and 100 µM As, it declined with the highest As treatment. As exposure caused a significant linear increase in proline content in the roots at both 15 and 30 days of treatment. The roots altered their internal structure by reducing diameter, cortical cell layers, lacunae in the cortex, and vascular tissue in response to As. Stem and leaf anatomy revealed that the primary site of As effect is the root, although it exhibited altered anatomy, particularly in vascular tissues, at the highest As concentration (150 µM).Bangladesh J. Bot. 55(1): 69-76, 2026 (March)